2021
DOI: 10.3390/d13120677
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sesamia nonagrioides (Lepidoptera: Noctuidae) EcR and USP Genes as Targets for Exogenous Non-Persistent RNAi

Abstract: RNA interference (RNAi) is a transforming technology with high potential for practical applications in biology, including specific and safe insect pest control. For developing RNAi-based pest-control products no general recommendations exist and the best strategy needs to be determined for each insect pest separately on a case-by-case basis. In this research, the potential of silencing the genes encoding the subunits of the ecdysone receptor complex, EcR and Ultraspiracle (USP) by RNAi was evaluated in the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…To evaluate the survival of 3 rd instar larvae, 200 μl of bacterially induced dsRNA as reported by [ 27 ] was compared with 15 μg of purified dsCHI. Previous studies have shown that lepidopterans are susceptible to high concentrations of dsRNA [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the survival of 3 rd instar larvae, 200 μl of bacterially induced dsRNA as reported by [ 27 ] was compared with 15 μg of purified dsCHI. Previous studies have shown that lepidopterans are susceptible to high concentrations of dsRNA [ 28 ].…”
Section: Methodsmentioning
confidence: 99%